Aukštaičių vaizdeliai, or On the Search for the Autobiography of Juozas Tumas-Vaižgantas - Raškevičiūtė, Jurgita Žana (Colloquia, 2024)
Juozas Tumas-Vaižgantas has the reputation of an autobiographical author who overshadows his texts. At the same time, he is an author without autobiography, whose epistolary works form the basis of his egodocumentary research. Keeping in mind the characteristic of this reception, I examine Vaižgantas’s autobiographical texts: compile a corpus of his autobiographical texts, and conduct a research of Tumas’ autobiographical narrative, with a focus on the speaker’s relationship to the autobiographical discourse. I began the search for author’s autobiography with the first text that has the status of an autobiographical narrative, Aukštaičių vaizdeliai (Scenes of Aukštaičiai). The research has revealed certain features of Tumas’ treatment of autobiographical texts that have not been studied in detail. The article presents the history of the formation, attempted publication and disassembling of Aukštaičių vaizdeliai. It describes Tumas’ attitude towards his autobiographical texts and raises the question of the boundaries between literary and autobiographical texts, revealing the author’s changing and individual relationship to autobiographical narrative. The research also points to a secondary effect of the research—the highly problematic identity of Aukštaičių vaizdeliai.